Firms' demand for employment-based mental health benefits - Shinogle, Judith A.; Salkever, David S. (National Bureau of Economic Research, 2005)
"Employment-based health insurance is the main source of health coverage for the non-elderly. Few previous studies have examined the factors that impact employer decision-making in selecting the coverage to offer to their employees and none have examined generosity of mental health coverage. This paper uses cross-sectional data from a survey of medium to large firms, including information on employee characteristics, to examine the empirical determinants of mental health coverage choices. We find that the firm's demand for mental health coverage is strongly influenced by employee characteristics. We also find that certain state and local policy interventions directed at enhancing access to mental health care have impacts on coverage decisions. Specifically, public provision of mental health lowers mental health coverage generosity and parity legislation increases mental health generosity. Future research with panel data is warranted to examine the causal effects of these policies"--National Bureau of Economic Research Web site.
Keywords: Health Benefit Plans, Employee -- United States; Insurance Coverage -- United States; Insurance, Psychiatric -- United States; Mental Health Services -- United States; Mental health insurance -- United States; Mental health policy -- United States; USA